2021
DOI: 10.3389/fphar.2021.623360
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Loneliness, Drug Craving, and Depression Among Substance Abusers in Sichuan Province, China

Abstract: Studies have reported that anxiety had a positive effect on depression among substance abusers in males. However, little is known about the mechanism underlying this relationship in substance abusers in males. The purpose of this study was to investigate the mediating effect of loneliness and drug craving between anxiety and depression in substance abusers in males. State-Trait Anxiety Inventory, The UCLA Loneliness Scale, Drug Craving Scale, and The Center for Epidemiologic Studies Depression Scale were emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…This study is one of the first to offer information about the relationship between loneliness and drug craving. Prior studies have reported loneliness and drug cravings as independently associated with depression and anxiety [ 65 ]. In fact, loneliness and drug craving have typically been coupled together and studied as a combined effect on substance use, depression, and anxiety [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is one of the first to offer information about the relationship between loneliness and drug craving. Prior studies have reported loneliness and drug cravings as independently associated with depression and anxiety [ 65 ]. In fact, loneliness and drug craving have typically been coupled together and studied as a combined effect on substance use, depression, and anxiety [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported loneliness and drug cravings as independently associated with depression and anxiety [ 65 ]. In fact, loneliness and drug craving have typically been coupled together and studied as a combined effect on substance use, depression, and anxiety [ 65 ]. While there is a direct relationship between loneliness and substance use itself [ 13 , 30 , 65 ], the relationship between loneliness and drug craving alone is understudied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UCLA Loneliness Scale comprises 20 items such as “Do you feel close to people?” and “Do you feel left out?” Patients rated each item on a 4-point scale, ranging from 1 ( never ) to 4 ( always ). Higher scores represent higher levels of loneliness (Chen et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Patients rated each item on a 4-point scale, ranging from 1 (never) to 4 (always). Higher scores represent higher levels of loneliness (Chen et al, 2021).…”
Section: Loneliness Assessmentmentioning
confidence: 99%